Properties of Brass under Different Pouring Temperatures in Sand Casting Process - Poppy Puspitasari; Avita Ayu Permanasari; Andoko Andoko; Bayu Angga Pratama (Journal of Mechanical Engineering Science and Technology (JMEST), 2017)
This study aimed to determine the toughness of casts produced by the sand casting process at various temperatures against brass, and to investigate the structure contained in the cast madeusing abrass metal mould. This study was experimental research that observed the results of a treatment applied to a specimen group. This pre-experimental study usedthe one-shot case study model in which a group of samples was given treatment. The results showed that the specimen poured at 900°C exhibiteda microstructure consisting ofgood Cu-Zn content, while that at 700°Chad the least Cu content. It indicates that the higher the temperature used for metal casting (brass), the more brittle the cast. The toughness of the materialwas influenced by the alloy composition and the pouring temperature of each specimen; the higher the pouring temperature, the better the treatment of alloy. The photomicrographs indicate that the higher the pouring temperature usedin the metal casting (brass), the lesser the carbon element contained in the material.